Políticas de currículo para o ensino médio : sentidos de educação no IFMT de Primavera do Leste (MT) - Silva, Eliane Aparecida da (2018)
This research is inserted in the Research Line Training of Teachers and Public Educational Policies of the Graduate Program in Education of the Federal University of Mato Grosso, Campus of Rondonópolis. It aims to investigate how education and / or vocational education integrated into Secondary Education is signified in the IFMT and what are the implications for education and curriculum in this institution. The research is based on analysis of the poststructural discursive discourse discourse, by Alice Casimiro Lopes and Elizabeth Macedo, and three contexts of Stephen Ball's policy cycle, Richard Bowe and Anete Gold: the context of influence, the context of the text production and the context of the practice. These contexts are composed of arenas and interest groups and each of them involves disputes and clashes in the production of politics. Focusing on the context of the production of the political text, I analyze normative documents (resolutions, opinions, guidelines), as well as other texts that guide the supply and attendance of high school and integrated secondary education in the municipality of Primavera do Leste - MT. In this first movement, I focus on aspects of educational reforms in Brazil, especially the reforms of secondary education directed at the Federal Institutes of Education in the midst of the main changes for Brazilian professional education in recent years, with emphasis on the place of curricular integration in the policies of this level. In a second movement of analysis, I seek to analyze the meanings of education in the IFMT Spring of the East, which I take as the context of practice in research. Focus on the privileged signifiers in political texts, on the intentions in dispute from such signifiers, in order to highlight the meanings of curricular change linked to the search for (good) quality of education. I dispute the disputes about the significant knowledge and knowledges that act as central in the attempt to hegemonize a meaning for education and try to demonstrate how these signifiers act in the attempt to close a single demand for quality education. I analyze the IFMT policy also discussing the meanings that practice subjects attribute to education and curriculum at this level of education. I emphasize the recurrence of the discourses around the better knowledge for the students of the High School Integrated to Professional Education as workers or as technicians, with skills and abilities considered necessary to the labor market and the productive world, pointing this meaning as a hegemonic sense of education in the politics of high school. I conclude by stating that if national and local policy, as the implications of the current senses, tends to accentuate the dualism in the Integrated High School to Vocational Education, it is because it is privileged to mean reduced education to the teaching of basic contents, of knowledge commissioned by the market in training of skills and skills for specific jobs. Defending the perspective of education as an event, I finally draw attention to the fact that in the daily educational process in the IFMT in focus there are other relationships being produced that partially escape this attempt to restrict the senses of education to behaviors and controllable skills, relationships that point to concerns about an education that put young people at the center as people in training.